Short Term Outcome of Drug Eluting Balloon for Percutaneous Coronary Intervention - Anwar, Maida; Nadeem, Asif; Rehman, Fahad Ur; Sarfraz, Sana; Ahmed, Iftikhar; Azad, Naseem; Siddique, Muhamad Bilal; Kamran, Javeria (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess the short-term outcome of Drug Eluting Balloon (DEB) for Percutaneous Coronary Intervention (PCI). Study Design: Analytical Cross-sectional study Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi, from Jan 2022 to July 2022. Methodology: Patients who underwent DEB-PCI within the past year were chosen via Universal sampling technique. Symptomatic patients were evaluated by conventional coronary angiography, while asymptomatic patients had CTangiography. Primary outcome was restenosis rate on angiographic follow-up. Patients having <30% visually estimated stenosis in the DEB treated artery were considered to have satisfactory results of DEB. Association of study’s variables with DEB outcome was determined by Chi-square test and p-value <0.05 was taken as significant. Results: Majority of patients were males 60(96.8%) and only 2(3.2%) were females. DEB outcome was satisfactory in majority of the study participants 48(77.4%). DEB was used in diagonal branch in majority of the cases 17(26.9%). In small vessels, 33(78.5%) patients showed satisfactory results while in large vessels 15(71.4%) patients had satisfactory outcome. No deaths or other complications related to procedure or device were reported. Out of total 62, 14(22.6%) patients showed unsatisfactory results with significant angiographic stenosis. Among these, 8(13%) patients were further treated with angioplasty and the remaining 6(9.6%) were left on optimal medical therapy. Significant association .... Conclusion: Study findings emphasized the safety and effectiveness of DEB as a possible treatment option for atherosclerotic CAD, ..